Biologi Reproduksi Rajungan (Portunus pelagicus) di Ekosistem Mangrove Kabupaten Labuhanbatu - Tianlin Munthe; Rivo Hasper Dimenta (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The purpose of this study was to analyze the Gonad Maturity Level (TKG), Gonad Maturity Index (IKG), first gonad maturity size (L50), egg weight (fecundity) in Portunus pelagicus in Sei Barombang waters, Labuhanbatu Regency. The sampling point for Portunus pelagicus sampling was carried out in Sei Barombang waters. The research method used purposive random sampling to determine three sampling stations in the research area. Portunus pelagicus samples were taken using traps and trawl nets. The results of the study of Portunus pelagicus males and females were more dominant in TKG I. The IKG values for male Portunus pelagicus ranged from 8.85 - 15.59 and females ranged from 5.15 - 13.69. The male Portunus pelagicus crab experienced the first maturity of gonads measuring around 87.20 mmCW and females around 103.55 mmCW. Egg weight or fecundity in Portunus pelagicus in Sei Barombang waters, Labuhanbatu Regency ranged from 317.280 ± 1.897558 eggs.